Síntese quimioenzimática de um precursor do fenilalaciclovir - Oliveira, Bruna Rocha de (2015)
Herein we describe the chemoenzymatic synthesis of a precusor of phenylalacyclovir (a substance with the potential activity for the treatment against herpes virus) containing seven chemical and one enzymatic steps. In order to obtain the target molecule was performed a C-alkylation reaction via Phase Transfer Catalysis (PTC) of diethyl Nacetamidomalonate in presence of N-benzyltributylammonium chloride (CBTBA), leading to ethyl 2-acetamido-2-cyano-3-phenylpropanoate in 72% yield. The latter was subjected to an acidic hydrolysis with formation of phenylalanine hydrochloride in a yield of 95%. Then phenylalanine hydrochloride was subjected to an esterification reaction in the presence of methanol (93% yield) and an N-acetylation (70% yield), yielding methyl 2-acetamido-3-phenyl-propanoate in racemic form. The strategy used to introduce chirality into the target molecule was the enzymatic kinetic resolution of methyl 2- acetamido-3-phenyl-propanoate via interesterification reaction. Only lipase from Rhizomucor miehei was able to promote the reaction in the presence of butyl butyrate using hexane as solvent. At this stage, (2S)-butyl -acetamido-3-phenylpropanoate was obtained with 48% conversion, enantiomeric excess (ee) > 99% and enantioselectivity (E) > 200. Then, (2S)-butyl-acetamido-3-phenylpropanoate was hydrolyzed to the corresponding acid in 66% yield. Finally, the precusor of phenylalacyclovir was obtained in 50% yield after a Steglish esterification of (2S)-acetamido-3-phenylpropanoic acid in the presence of acyclovir, dicyclohexylcarbodiimide (DCC) and N,Ndimethylaminopyridine (DMAP).